Optimasi Penugasan Mekanik Menggunakan Metode Hungarian pada Dealer AUTO 2000 di Kota Padang - Winanda, Rara Sandhy; Defitri, Fanessa Elrika; Rahmawati, Rahmawati (Jurusan Matematika, Fakultas Sains dan Teknologi, UIN Sunan Gunung Djati Bandung, 2023)
Efficient placement of mechanics at Auto 2000 Dealer in Padang City has a significant impact on the productivity and profitability of the company. In this study, we propose the implementation of the Hungarian Method as an optimization tool to determine the optimal assignment of mechanics. The study involves five variables that, respectively, represent the availability of mechanics and various types of serviced vehicles. The goal is to minimize service time in order to optimize the number of vehicles that can be serviced per month. In this research, we utilize historical data that is collected from Auto 2000 dealers to analyze the performance of mechanic placement. The results show that by implementing optimal mechanic assignments using the Hungarian Method, the company can improve efficiency of service time as well as increase the number of vehicle units to be serviced per month to 1.957 units.